Human Resource Management in Professional Service Firms: Learning from a Framework for Research and Practice. (May 2015) - Kaiser, Stephan; Kozica, Arjan; Swart, Juani; Werr, Andreas
Success in human resource management (HRM) depends on the question of whether applied practices of HRM meet specific contingency factors and are appropriately configured. Using this argument, the present article examines HRM in professional service firms (PSFs) in pursuit of three objectives. First, we introduce a conceptual framework that illustrates how the constitutive characteristics of PSFs, as contingency factors, influence HRM practices and research. Second, based on this framework, we summarize key findings of research on HRM in PSFs and open up potential avenues for further research. Third, we reflect on the argument that HRM in PSFs can contribute to an understanding of HRM practices in other organizational settings, leading to the question of the mutual transferability of HRM practices. Aside from these three primary objectives, we also introduce the contents of the special issue.